№65
Рейтинг: 0.0 з 5 (0 голос.)

1) (x + 4)(x + 1) = x – (x – 2)(2 – x);
x2 + x + 4x + 4 = x – 2x + x2 + 4– 2x;
8x = 0; x = 0.

2) (x – 9)(x – 1) = x – (x – 3)(3 – x);
(x – 9)(x – 1) = x + (x – 3)2;
x2x – 9x + 9 = x + x2 – 6x + 9;
–5x = 0; x = 0.

3) (x + 2)(x + 8) = 3x – (4 – x)(x – 4);
(x + 2)(x + 8) = 3x + (4 – x)2;
x2 + 8x + 2x + 16 = 3x + 16 – 8x + x2;
15x = 0; x = 0.

4) (x – 4)(x – 9) = 7x – (6 – x)(x – 6);
(x – 4)(x – 9) = 7x + (6 – x)2;
x2 – 9x – 4x + 36 = 7x + 36 – 12x + x2;
–8x = 0; x = 0.

Відгуки

Всього коментарів: 0
avatar

Відгуки

avatar
up